Efektivitas Model Flipped Classroom untuk Pengajaran Alat Musik Tradisional Aceh secara Daring - Ilham Septian; Samsuri Samsuri; Yuli Astuti (Pusat Riset dan Inovasi Nasional, 2025)
The flipped classroom model emerges as an innovative pedagogical approach that fosters active student participation and cultivates personal responsibility for learning, particularly within the context of distance education. This method presents a valuable alternative for delivering practical-oriented courses such as Applied Ethnomusicology. In practice, the instructor’s role shifts from a traditional knowledge transmitter to a learning facilitator whose responsibilities include guiding, inspiring, and supporting students in achieving optimal learning outcomes. This study aims to analyze the effectiveness of implementing the flipped classroom model in the online learning of the rapa’i musical instrument at the Department of Performing Arts, Syiah Kuala University. Additionally, it seeks to describe the subjective perceptions and responses of both students and lecturers toward this instructional approach. Online learning was conducted using Zoom Meeting as the primary platform for synchronous interaction, supported by WhatsApp for content distribution and communication. A formative research methodology was employed, involving 20 students enrolled in the Applied Ethnomusicology course. Qualitative data were collected through observations of each flipped classroom phase and in-depth interviews with participants. Quantitative analysis was conducted to assess effectiveness via N-gain calculations. Results indicate that all stages of the flipped classroom model were successfully implemented, and the online learning process proceeded adequately despite challenges such as limited internet access and the scarcity of personal rapa’i instruments. Quantitatively, the model demonstrated moderate effectiveness, with an N-gain value of 0.3. Overall, students displayed high levels of enthusiasm and consistent engagement during each learning session, reflecting a significant increase in learning involvement.